Modeling of Passenger Ride-Comfort Enhancement through Designing Seat Cushion with Scilab-Xcos - Vito; Mochamad Januar; Purnomo Sejati (Department of Mechanical Engineering Atma Jaya Catholic University of Indonesia, 2018)
This paper demonstrates a modeling of vehicle ride comfort using 11 degrees of freedom (DoF) quarter-car approximation with a free and open-source Scilab-Xcos software. The simulation is aimed to enhance the ride quality of passengers by optimizing parameters of the seat cushion in the seat structure of the vehicle. From the simulation results, the seat cushion plays an important role in improving the ride comfort of the passenger. A significantly lower vertical displacement and acceleration were observed on the occupant’s head relative to the model without seat-cushion. Moreover, the ride comfort can be further increased by optimizing the parameters in the seat cushion. The lowest vibration peaks were attained from the combination of the stiffness of 16 N/m and damping of 25 Ns/m. However, variations of the mass of the seat cushion are found to give insignificant effect on the comfort improvement.